Elimination of Sulfamethoxazole by Anodic Oxidation Using Mixed Metal Oxide Anodes - Huilinir-Curio, C; Sepúlveda-Ortiz, P; Sepúlveda-Ortiz, P; Lauzurique-Guerra, y (Elsevier Ltd, 2023)
The degradation of sulfamethoxazole (SMX) was studied by anodic oxidation (AO) process using mixed metal oxide (MMO) electrodes with different Ru/Ir ratios. Each electrode was characterized morphological and electrochemically. The electrolyzes were performed in NaCl and Na2SO4 applying two current densities (10 and 50 mA cm−2). The electrode with the highest composition of Ir, Ru/Ir (30/70), showed greater SMX degradation and generation of oxidizing species and was used to treat the antibiotic by AO and AO assisted by solar energy in natural water and actual municipal wastewater effluents. The efficiency in SMX degradation depends on the type of electrode used (MMO) and electrolytic medium. All MMO electrodes, reached almost total degradation of SMX in chloride medium. However, 60 % degradation of SMX in sulfate medium was achieved with anode with lower Ru/Ir ratio. Additionally, degradation of SMX in complex matrices can be successfully carried out by solar-assisted AO and AO processes, without the need to adjust the pH, at room temperature and using anode with lower Ru/Ir ratio. Finally, the AO process assisted by solar energy reduced electrolysis times and the cell s potential, leading to lower energy consumption. © 2023